EXPERIENCES OF NURSES EXPERIENCING VIOLENCE IN THE EMERGENCY ROOM: A QUALITATIVE STUDY - Fakrul Ardiansyah; Revani Hardika; Tika Desvicasari Hustra (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Background: The phenomenon of violence against nurses is even higher. Still, the results of the study are 80% of nurses who experience violence do not report the incident, nurses take compensatory actions such as sick leave, fear, and lack of support from hospital administration Objectives: Researchers explored the experience of nurses and the need for more effective protection for emergency unit nurses, this is very important to understand the experiences of nurses who experience violence in the emergency unit. Methods: The qualitative approach that will be used is transcendent phenomenology (descriptive phenomenology). The population in this study were all emergency unit nurses at the Pontianak City government-owned hospital. Total 15 participants. The criteria for the participants were emergency unit nurses, nurses with experience of acts of violence by others, age > 20 years, and willingness to become participants. The sampling technique used is purposive sampling. Researchers conducted interviews based on the guidelines that had been prepared. The ethical principles were applied on this study. The stages of data analysis in this study are based on the stages of Colaizzi Results: The results of this study describe the phenomenon of the experience of nurses who experience violence in the Emergency Unit. The five themes include (1) The working period of nurses who experience violence in the Emergency Unit; (2) Causes of nurses experiencing violent behavior in the emergency department; (3) Forms of violent behavior towards nurses in the emergency department; (4) The attitude of nurses who experience violence in the emergency unit; and (5) Protection of nurses in the emergency department Conclusion: It is believed that nurses who experience violence do not disclose it to management because there is a lack of management support and unclear reporting guidelines. The suggestions are that the management of and prevention of violence against nurses in Indonesia therefore requires management support, documented policies, clear reporting procedures, security systems in hospitals, and clear legal protection by leadership and Indonesian National Nurses Association.